Family Size and Children's Education: Evidence from the One-Child Policy in China - Yue Huang (Population Research and Policy Review, 2021)
Evidence on a causal link between family size and children's education is still inconclusive. Recent empirical studies have focused heavily on China, exploiting for identification the country's One-Child Policy (OCP) as an exogenous source of variation in the number of offspring. This literature, however, suffers from measurement error in the key policy variable (individual OCP coverage) and the use of inadequate measures of child quality outcomes (educational attainment). Using a novel and more accurate taxonomy of provincial OCP regulations and studying exclusively post-compulsory schooling outcomes of children that are subject to parental discretion, we find evidence for a sizeable child quantity–quality trade-off in China. Various robustness checks corroborate this conclusion.
Keywords: J13; J18; I2; 300; Family size; Education; One-Child Policy; Quantity–Quality Trade-Off